FAKTOR SOSIAL EKONOMI DAN PENDAPATAN USAHATANI PADI SAWAH TADAH HUJAN KABUPATEN BARRU - Arifin, Arifin (Universitas Galuh, 2023)
The socio-economic condition of farmers is the position or position of farmers in society related to internal factors or level of education, type of work, number of family members, and land ownership. Income can be used as an indicator in determining the level of success in a farming activity, as well as being an important factor in determining the sustainability of a farming business. The purpose of this study was to analyze the socioeconomic factors that influence the income of rainfed lowland rice farming and to analyze the income of rainfed lowland rice farming. This research was conducted in Sape'e Village, Barru District, and Lompo Tengah Village, Tanete Riaja District, Barru Regency. The study population was 228 people and the number of samples was 50 people. Farmer samples were taken using a multi-stage cluster random sampling technique. Data collection techniques used are observation/observation, interviews, and documentation. Data sources are primary and secondary data. The data analysis method used is multiple regression analysis and income. The results of this study indicate that the socio-economic factors that influence the income of rainfed lowland rice farming in Barru Regency are education, land area, and farming experience. The income of rainfed lowland rice farming in Barru Regency is Rp. 4,772,703.00/PS.